2013
DOI: 10.1097/01.sa.0000426602.85890.2b
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative QT Interval Prolongation in Patients Undergoing Noncardiac Surgery Under General Anesthesia

Abstract: Background-Abnormal cardiac repolarization, indicated by a prolongation of the QT-interval, increases the risk for torsade de pointes, a potentially life-threatening arrhythmia. Many perioperatively administered drugs and conditions prolong the QT-interval. Despite several reports of perioperative torsade de pointes, systematic evidence regarding perioperative QT-interval prolongation is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…In addition to voriconazole, our patient had several other risk factors for QTc prolongation including transient hypomagnesemia, diabetes, female gender, receipt of perioperative anesthetics, and multiple arrhythmogenic medications, including azithromycin and ciprofloxacin . Both azithromycin and fluoroquinolones have been shown to increase QTc prolongation .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition to voriconazole, our patient had several other risk factors for QTc prolongation including transient hypomagnesemia, diabetes, female gender, receipt of perioperative anesthetics, and multiple arrhythmogenic medications, including azithromycin and ciprofloxacin . Both azithromycin and fluoroquinolones have been shown to increase QTc prolongation .…”
Section: Discussionmentioning
confidence: 92%
“…QTc prolongation is a common and potentially life‐threatening condition in patients who undergo solid organ or hematopoietic stem cell transplantation. The reasons for this are not entirely understood, but may include perioperative QTc‐prolonging medications and electrolyte imbalances . Other well‐described risk factors for post‐transplant QTc prolongation include structural heart disease, cardiac ischemia, thyroid disease, diabetes mellitus, female gender, and heritable cardiac syndromes …”
Section: Discussionmentioning
confidence: 99%
“…Extrapulmonary side effects are mediated by the spillover of cytokines toward the systemic circulation, and may include liver injury, natural‐killer cell impairment and arrhytmias . The latter also include transient QT‐tract prolongation, which has been shown to occur in up to 80% of patients with possible evolution to torsade de pointe in 0.4% of these …”
Section: Injurious Effects Of General Anesthesia (Ga) and One‐lung Vementioning
confidence: 99%
“…reported that QTc prolongation was common 30 minutes post‐operatively and likely due to medications given during surgery or surgical stress . This study was done on approximately 500 adult patients undergoing noncardiac surgery; one of these patients had an increase in QTc from 439 to 468 ms and developed TdP . As a result, in our denervation program, we try to avoid as much as possible agents that will stimulate sympathetic tone.…”
Section: Discussionmentioning
confidence: 99%